2000
DOI: 10.1038/35050598
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of microtubules and the actin cytoskeleton by the Rho effector mDia1

Abstract: Coordination of microtubules and the actin cytoskeleton is important in several types of cell movement. mDia1 is a member of the formin-homology family of proteins and an effector of the small GTPase Rho. It contains the Rho-binding domain in its amino terminus and two distinct regions of formin homology, FH1 in the middle and FH2 in the carboxy terminus. Here we show that expression of mDia1(DeltaN3), an active mDia1 mutant containing the FH1 and FH2 regions without the Rho-binding domain, induces bipolar elo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
251
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(270 citation statements)
references
References 38 publications
17
251
0
2
Order By: Relevance
“…Previous studies in HeLa cells demonstrated that exogenously introduced mDia localized to the perinuclear zone and to podosome-like regions in the periphery of the cell (28). Our data show that both endogenous and overexpressed mDia localize to the leading edge, but only scarcely at the leading lamella.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Previous studies in HeLa cells demonstrated that exogenously introduced mDia localized to the perinuclear zone and to podosome-like regions in the periphery of the cell (28). Our data show that both endogenous and overexpressed mDia localize to the leading edge, but only scarcely at the leading lamella.…”
Section: Discussionsupporting
confidence: 46%
“…The activated mutant of p160ROCK (⌬4-ROCK) and the kinase-dead mutant (KD-ROCK) have been previously described (33). The wild-type enhanced green fluorescence protein (EGFP)-mDia, activated mutant EGFP-mDia ⌬N3, EGFP-mDia F2, and EGFP-mDia ⌬N3 (HindIII) have been described previously (18,28). EGFP-mDia F1 (aa 570 -735) was generated by PCR (primers 5Ј-GGAA GATCTGCTGCTGTTCCCCTG-3Ј and 3Ј-AGGGGGCCCAAATCCAAA GGGGGGAGGT-5Ј), cloned in-frame in BglII/SmaI of the multiple cloning site of pEGFP-C1, and confirmed by sequencing.…”
Section: Cdna and Transfectionmentioning
confidence: 99%
“…In this system, Rok activates the actin-based molecular motor myosin II to exert tension force on actin filaments during stress fiber formation, whereas Dia1 seems to contribute to the determination of nucleation sites for actin filaments. More recent studies in fibroblasts and HeLa cells demonstrate a role for Dia1 as mediator of RhoA's effects on microtubule stabilization in the leading edge (Ishizaki et al 2001;Palazzo et al 2001a). Based on these observations, it has been speculated that Dia1 could play a role in regulating the assembly or maintenance of the hair cell cytoskeleton (Müller and Littlewood-Evans 2001).…”
Section: Planar Polaritymentioning
confidence: 99%
“…The FH1 domain binds profilin, an actin-binding protein (20), and Src homology 3 domains containing proteins such as Src (28) and IRSp53/BAIAP2 (29). The FH2 domain has been reported to be involved in coordinating microtubules and the actin cytoskeleton during cell movement (30). mDia1 contains a 173-amino acid region in the C terminus of its FH3 domain that is necessary for mDia1 localization to mitotic spindles in HeLa cells (31).…”
mentioning
confidence: 99%